2002
DOI: 10.1385/abab:98-100:1-9:415
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Microbial Dehydrogenase A Vanillin:NAD(P)<sup>+</sup> Oxidoreductase

Abstract: Pseudomonas fluorescens (strain BTP9) was found to have at least two NAD(P)-dependent vanillin dehydrogenases: one is induced by vanillin, and the other is constitutive. The constitutive enzyme was purified by ammonium sulfate fractionation, gel-filtration, and Q-Sepharose chromatography. The subunit Mr value was 55,000, determined by sodium dodecyl sulfate polyacrylamide gel electrophoresis. The native Mr value estimated by gel-filtration chromatography gave a value of 210,000. The enzyme made use of NAD+ les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…This is in agreement with both the calculated molecular mass of the vdh translational product and the sizes of other enzymes exhibiting VDH activity (18,32,35,36). The recombinant protein carrying a His 6 tag was purified to apparent homogeneity, which was confirmed by immunodetection.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This is in agreement with both the calculated molecular mass of the vdh translational product and the sizes of other enzymes exhibiting VDH activity (18,32,35,36). The recombinant protein carrying a His 6 tag was purified to apparent homogeneity, which was confirmed by immunodetection.…”
Section: Discussionsupporting
confidence: 83%
“…Besides the in silico analyses, the specific vanillin dehydrogenase activity in cells of Amycolatopsis sp. ATCC 39116 was investigated after cultivating the strain with or without vanillin and structurally related compounds like ferulic acid as the carbon source, since previous investigations with Pseudomonas showed an inducing effect (27,32). Amycolatopsis sp.…”
Section: In Silico Analyses Of the Genome And Identification Of The Amentioning
confidence: 99%
“…5b ), which indicated that VDH from NL15-2K is a tetramer. This was in agreement with previous reports that VDHs from P. fluorescens BTP9 [ 34 ] and Micrococcus sp. TA1 [ 35 ] are tetrameric enzymes.…”
Section: Resultssupporting
confidence: 94%
“…The VDH enzyme assay was performed based on described methods 32 33 34 in 100mM potassium phosphate buffer (pH 7.0). The activity of vanillin dehydrogenase was monitored spectrophotometrically by measuring the rate of decrease in absorption at 340nm due to oxidation of NAD(P)H and was calculated with an extinction coefficient of 6,220M 1 cm 1 .…”
Section: Methodsmentioning
confidence: 99%
“…HR199 24 , VDH of Amycolatopsis sp. ATCC 39116 21 , VDH of Pseudomonas fluorescens 32 44 , aldehyde dehydrogenase (NAD + ) of Pseudonocardia sp. P1(ZP_08121488.1), benzaldehyde dehydrogenase (NAD + ) of Saccharopolyspora erythraea NRRL 2338(YP_001105347.1), benzaldehyde dehydrogenase (NAD + ) of Burkholderia cenocepacia AU 1054(YP_621190.1), and aldehyde dehydrogenase of Amycolatopsis mediterranei U32 (AMED_0881).…”
Section: Figurementioning
confidence: 99%